Implementación del área de conservación privada en la cuenca alta del Río Verde, valle de los Chilchos y la meseta, Saposoa - Salas Guerrero, Marcos (2014)
The implementation of the Prívate Conservation Area is located in the upper basin of the Rio Verde, between the Chilchos valley and the Meseta, west of the San Martín region (77°41'36.30"- 7r36'11.77" W, 6°49'41.60"- 6°43'32.65" S) between the altitudes of 1500 up te the 3627 m.s.n.m., Yasgolga mountain chain, it is a branch very integrated te the Northeastern Mountain chain of the Andes of Peru that one understands on brought near of 500.00 hectares delimitad by the Marañan, Utcubamba, Huayabamba and Huallaga rivers, north of the National Park Abiseo river. By their relativa isolation has a high biological value, ecological and archaeological, with forest fragile and irreparable, own of cloud forest, has been included in the list of the 38 priority areas for conservation by the great biological diversity at the national leve! (Master Plan 2009). lt has been many years of research and negotiation between the state and the organizations to determine a strategy for the conservation of a portian of the Eastern Cordillera of the Andes of Peru, a product of this effort is today the National Park Abiseo River. However, it is well known that the ecological processes do not know borders or administrativa policies, and an ecosystem of humid forest, such as the Chilchos, Huabayacu and Jelache (high basin of the Huallaga River), still need other complementary strategies to ensure the conservation of these wetland ecosystems and fragile. Taking into account this prioritization, necessity and through an exemplary initiative of the local population in the Chilchos valley, which is located in this part of the Yasgolga Cordillera, is looking for the deployment of Prívate Conservation Area, due te the demographic pressure disorderly migration toward this area of the North slope, in search of new lands, following ancient modes of agricultura! production that will seriously affect the moist montana forests of the Chilchos vaUey and the Meseta. The growth of the human impact towards this zone during the last decades has caused that performs vital importance the intervention of the Authorities and put into practica the minimization of these processes, across the conservation of the biological, ecological and archaeological values, by means of the impulsamiento of creation of air of conservation, en the basis of he her would play low that they possess these places befare mentioned. The first step for the creation of areas and conservation of the biological resources, it has been to raise the bordering, social, cultural, economic and environmental information and especially the preliminary inventaries in different sectors and to establish the implementation of the Area of conseri.tation in the high basin of the Green river, the Chilchos valley and the Meseta. These sectors were 1 ) the surroundings of the Lagoon of the Condors and the Lead, between 2900 to 3350 meters of altitude, 2) around the Chilchos, on the Chilchos river and one on the Blanco river, both between the 1550 and 1900 meters above sea level, 3) around Anasco People, between 1900 and 2570 meters of altitude, and 4) around the area known as the Laurel, between 2700 to 3200 m of altitude. The data obtained in this preliminary inventory corroborated with the inventory of the 2003, 2008, and 201 O, show a great biological value, a high endemism anda high percentage of threatened species (D. S. No 034-2004-AG y D.S. 043- 2006-AG), but at the same time a high threat of destruction of the cloud forest, its diversity and the archaeological sites present throughout the Green River basin. In the same shipment were used to inventory through coordinates the archaeological sites, which include severa! sites preyed funeral and sorne sites intact, which however is under the threat of predation. Key words: disorderly migration, threatened species. JR.